Isolation Of Dermatophytes From Infected Stray Cats In Selangor - P.M Ridzuan; Manuel Ruth; Kamarulzaman Siti-Arffah (Jurnal Berkala Epidemiologi, 2021)
Background: Dermatophytosis is the most prevalent fungal infection found in cats and one of the most serious infectious skin diseases that affect this species. Dermatophytosis can be endemic in cats, particularly in poor environments, and it is difficult to eradicate in such cases. Purpose: The aim of this research was to determine the macroscopic and microscopic identification of various types of dermatophytes present in stray cats. Methods: The research was designed as a laboratory-based study. The sample was determined through physical examination of stray cats infected with fungi and was selected based on the infection site (nail, hair, and skin) of infected cats. A total of 125 samples were collected from infected stray cats through skin scraping, haircutting, and nail clipping. The collected samples were then cultured in Sabouraud Dextrose Agar (SDA) medium and incubated for two weeks at 26°C. Following incubation, fungi were stained using Lacto-phenol Cotton Blue (LPCB) for microscopic identification. Results: The identification showed that Trichophyton spp. is the most common isolated fungal species on the hair, nails, and skin of stray cats. This is followed by Aspergillus spp. and Microsporum spp. The least common dermatophytes include Curvularia spp., Absidia spp., Epidermophyton spp., Neosytallidium spp., Alternaria spp., Scopulariopsis spp., Mucor spp., and Penicillium spp. Conclusion: The research focussed exclusively on stray cats with clinical evidence of mycotic lesions and confirmed the role of stray cats in transmitting dermatophytosis through their hair, nails, and skin. The prevalence of dermatophytes on stray cats was identified in the Selangor region.